Archery's signature: an electromyographic analysis of the upper limb. (26th May 2022) - Dorshorst, Tabitha; Weir, Gillian; Hamill, Joseph; Holt, Brigitte
Abstract: Abstract: Non-technical summary: Bow and arrow technology plays a significant role in the recent evolutionary history of modern humans, but limitations of preservation make it challenging to identify archaeological evidence of early archery. Since bone structure can change in response to muscle force, archers of the past can potentially be identified through analysis of upper arm bones. However, there is limited research on how archery impacts upper limb musculature. This study offers initial insights into how archery impacts humeral musculature and highlights the need for additional research focused on archery's direct impact on humeral morphology. Technical summary: Humeral morphology has been used to support behaviour reconstructions of archery in past populations. However, the lack of experimental research concerning the impacts that archery has on the upper limb weakens skeletal morphological approaches. The goal of this study was to determine how archery impacts the activation of upper limb musculature. More specifically, this study tested: (a) whether the relative muscle activations are similar between arms; and (b) what muscles were activated on the dominant (draw) arm compared with the non-dominant (bow) arm. Data on upper arm muscle activation were collected bilaterally for nine archers using surface electromyography (EMG). Results show similar levels of muscle activation bilaterally with different muscles being activated in each arm. There were significantly higher integrated EMG and peak muscle activations of the biceps brachii muscles in the draw arm compared with the bow arm. In contrast, the lateral deltoid and the triceps brachii muscles had significantly higher integrated EMG and peak muscle activations on the bow arm compared with the draw arm. This work offers initial insights into how archery impacts humeral musculature and highlights the need for additional research focused on archery's direct impact on humeral morphology.